MENGEMBANGKAN KETERAMPILAN DASAR MENGAJAR GURU PADA SEKOLAH DASAR DI KELAS RENDAH - Nur Wahyuni (Universitas Negeri Medan, 2022)
Besides having to master the material, the teacher must also master the basic skills of teaching, so that they can carry out their role optimally. However, there are teachers who have difficulty in applying basic teaching skills in schools or there are still many obstacles that prevent teachers from developing their basic teaching skills. For this reason, this study aims to find out how to develop basic teaching skills for teachers in lower grade elementary schools that can be a source of reference and information for readers. Based on the author's observations in learning, it is known that knowledge about basic skills of teaching in lower grades is still very minimal, this is evidenced in the limited skill performance activities by researchers whose components in each skill are neglected. Practically, the provision of teaching skills can be trained through microteaching activities or micro teaching. The subject of this research is the teacher/prospective teacher in developing basic teaching skills. In this study, researchers used descriptive qualitative research methods and literature study. The procedure carried out is by observing data from various sources related to the problem of teacher difficulties/obstacles in applying basic teaching skills in low-grade elementary schools, then the author develops an idea to raise a study on how to develop basic teaching skills of a teacher in elementary schools. low class.